2019
DOI: 10.1186/s40249-019-0599-4
|View full text |Cite
|
Sign up to set email alerts
|

Neglected tropical diseases in the People’s Republic of China: progress towards elimination

Abstract: Since the founding of the People's Republic of China in 1949, considerable progress has been made in the control and elimination of the country's initial set of 11 neglected tropical diseases. Indeed, elimination as a public health problem has been declared for lymphatic filariasis in 2007 and for trachoma in 2015. The remaining numbers of people affected by soil-transmitted helminth infection, clonorchiasis, taeniasis, and echinococcosis in 2015 were 29.1 million, 6.0 million, 366 200, and 166 100, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 46 publications
1
38
0
3
Order By: Relevance
“…Out-of-pocket payments trap poor and near-poor households in a vicious cycle due to large personal expenditures leading to impoverishment and worse health, particularly in the LMICs where social health insurance schemes are generally lacking. Besides the NCDs and major infectious diseases, the NTDs constitute a group of diseases in tropical environments closely associated with poverty proliferation [9,17]. Although many countries have made progress in the elimination of NTDs, an estimated 1.5 billion people in 2016 still require treatment and care due to affliction with one or more NTDs, among them about 400 million (27%) in low-income countries [4], emphasizing the worldwide presence of poverty and inequality.…”
Section: Poverty Leads To Illnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Out-of-pocket payments trap poor and near-poor households in a vicious cycle due to large personal expenditures leading to impoverishment and worse health, particularly in the LMICs where social health insurance schemes are generally lacking. Besides the NCDs and major infectious diseases, the NTDs constitute a group of diseases in tropical environments closely associated with poverty proliferation [9,17]. Although many countries have made progress in the elimination of NTDs, an estimated 1.5 billion people in 2016 still require treatment and care due to affliction with one or more NTDs, among them about 400 million (27%) in low-income countries [4], emphasizing the worldwide presence of poverty and inequality.…”
Section: Poverty Leads To Illnessmentioning
confidence: 99%
“…However, this kind of poverty-related lack of proper care is still a challenge in China and to eliminate infectious diseases among the poor and improve their accessibility and affordability with respect to disease prevention, treatment and rehabilitation services will take more time [25]. For example, the results from three rounds of a national survey of important parasitic diseases showed that with the economic development, the average prevalence rate of soil-transmitted helminthiasis dropped from 59.8% in 1991 to 19.6% in 2003, and continued down to 4.8% in 2013 [9]. Another example is malaria, a disease with high mortality that traps households in poverty in many countries with a high burden of this infection [26][27][28], where Chinese evidence shows a significant Spearman's rank correlation coefficient correlations between poverty and incidence of malaria (0.88, P < 0.01), as well as between poverty and epidemic hemorrhagic fever (0.89, P < 0.01) for the years 1990-2018 [15,[29][30][31] (Fig.…”
Section: Poverty Leads To Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to lift the impact of RNAS+, as a platform for exchange and dissemination of information on schistosomiasis and other zoonotic helminthiasis control, which breaks the geographic borders to encouraging the collaboration and communication among scientists and decision-makers [24], several ways to enhance China's contribution to RNAS + development in future were suggested. First, China has made great progress in Schistosomiasis control in the past 70 years [25][26], continuing seeking out professional integrating points to share China's experiences and enhance the cooperation within member countries is still the signi cant issue [27][28]. Second, capacity building is needed by RNAS + members, China can continue to support the annual workshops and technical trainings as well as collaboration research [29][30].…”
Section: Challenges and Suggestions For Rnas + Developmentmentioning
confidence: 99%
“…The dietary habit of ingesting raw freshwater fish could date back to one century ago there [12]. Following the development of aquaculture, the endemicity is worsen in some areas because of the more accessibility to freshwater fish [13,14]. The epidemiology of clonorchiasis is characterized by the increasing prevalence and intensity by ages and higher prevalence and intensity in males compared to females [7,11,13].…”
Section: Introductionmentioning
confidence: 99%